2016
DOI: 10.1177/0144598716629872
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency assessments for some state of the art wind turbines in the coastal environments of the Black and the Caspian seas

Abstract: The main objective of the present work is to assess the wind energy resources in the Black and in the Caspian seas. Additionally, the electric power expected to be provided by various state of the art technologies was also evaluated. For this reason, several reference points were considered in the coastal environments of the two areas targeted. In order to assess the wind potential in these locations, 12 year of data coming from the US National Centers for Environmental Prediction were processed and analyzed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 32 publications
1
37
1
Order By: Relevance
“…Many previous studies, related to the wind energy potential [4][5][6][7][8][9][10], showed that the coastal environment of the Black Sea, and especially its northern and western side, is fully appropriate for the implementation of offshore wind projects. Furthermore, various studies have been also carried out related to the climate change impacts on wind energy potential in the Black Sea [49,50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many previous studies, related to the wind energy potential [4][5][6][7][8][9][10], showed that the coastal environment of the Black Sea, and especially its northern and western side, is fully appropriate for the implementation of offshore wind projects. Furthermore, various studies have been also carried out related to the climate change impacts on wind energy potential in the Black Sea [49,50].…”
Section: Discussionmentioning
confidence: 99%
“…This means the offshore wind becomes now not only the cheapest marine renewable energy resource, but it is also cheaper than some traditional resources. For example, the current average LCOE for atomic energy is still about 11 c€/kWh, or greater [3].Various studies [4][5][6][7] showed that the wind energy resources along the coasts of the Black Sea, and especially in its western side, are comparable with those from many offshore wind farms that are already operational [8][9][10][11]. Thus, it is expected that the high dynamics of the offshore wind industry will have as a result also the implementation of some wind farm projects in the nearshore of the Black Sea, in general and in its western side, which is more energetic, in special.…”
mentioning
confidence: 99%
“…The first one is the wind power density (WPD) index, which is frequently used to identify the energy potential of a particular site by evaluating the energy concentrated in the air flow. It can be defined by the following expression [66]:…”
Section: Era-interim Global Wind and Wave Datamentioning
confidence: 99%
“…Similar to the Beaufort scale, which describes the empirical correlation between the wind speed and a particular sea state [73], also the wind energy potential of a particular site can be identified throughout the wind power classes denoted from C1 to C7 [64][65][66]74], where the latest one represents the most attractive from an energetic perspective. In Table 2 The wind conditions from the intervals 6-9 m/s and higher than 9 m/s are encountered more often, except for the sites AM1, AF1, AF2, AF4, AS3, and AS4, where the interval 3-6 m/s seems to be dominant.…”
Section: Analysis Of the Wind Conditionsmentioning
confidence: 99%
“…Reported in the year 2018, there is some interest to implement wind projects in (semi) enclosed seas, this being the case of the North (62%), Irish (15%), and Baltic Sea (14%) while on the opposite side of the Atlantic Ocean is located with only 9% [14]. Beside these regions, some other important basins may become attractive for the implementation of an offshore project, from which we can mention the Mediterranean, Caspian or Black seas [15][16][17].…”
Section: Introductionmentioning
confidence: 99%